Sustainability Practices: Implementing Green Marketing through Eco-Friendly Packaging to Minimize Negative Impacts on the Environment (Case Study: PT. Sinar Sosro Ungaran) - Ainur Hidayah, Shafna; Pratiwi, Ratih; Purnomo, Mochammad (International Journal of Management, Business, and Social Sciences, 2025)
Increasingly pressing environmental issues require companies to implement sustainable business practices. Unsustainable packaging significantly contributes to soil, water, and air pollution, disrupts ecosystems, increases health risks from microplastics and hazardous chemicals, increases the economic burden of waste management, and accelerates climate change through increased greenhouse gas emissions. Green marketing and the use of eco-friendly packaging are effective strategies for reducing the negative impacts of business activities on the environment. This study aims to analyze the implementation of green marketing practices through eco-friendly packaging at PT Sinar Sosro Ungaran and evaluate its effectiveness in minimizing negative impacts on the environment. The research approach used was a qualitative case study at PT Sinar Sosro Ungaran. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman method through the stages of data reduction, data presentation, and conclusion drawing. The results show that PT Sinar Sosro Ungaran has implemented an effective green marketing strategy, including the use of eco-friendly packaging that contributes to plastic reduction, increased recycling of materials, and increased environmental awareness among consumers. Implementing green marketing through eco-friendly packaging not only benefits companies but also significantly contributes to minimizing negative environmental impacts. Recommendations for companies include further development of sustainability strategies, while further research is recommended to explore the long-term impact of this practice on consumer behavior and the environment. Keywords :Sustainability; green marketing; eco-friendly packaging; PT Sinar Sosro Ungaran; environmental impact.